The reception and integration process of refugees and asylum seekers in Bizkaia: a reality with a variable geometry? - La Spina, Encarnación; Vicente, Trinidad L.; Urrutia, Gorka; Morondo, Dolores (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2018)
The processes of reception and integration are not only a complex and variable reality in the European Union but particularly in specific social contexts, such as cities and provinces. These must face the daily challenges of meeting the particular needs of refugees, ensuring daily coexistence. This paper presents the results of an interdisciplinary research on the degree of implementation of the reception and integration processes in Bizkaia, paying attention at the different phases of the Spanish Reception and Integration System for international protection applicants and beneficiaries. For that purpose, the capacity of recently launched programs, including the Goihabe Program, is analyzed in order to optimize the coordination and integral management of these processes in Bizkaia.
Keywords: refugees; integration; reception; processes; Bizkaia